Oxytocin Receptor Polymorphism Decreases Midline Neural Activations to Social Stimuli in Anorexia Nervosa - Sala, Margarita; Han, Kihwan; Acevedo, Summer; Krawczyk, Daniel C.; McAdams, Carrie J. (Frontiers in Psychology, 2018)
Oxytocin is a neurotransmitter related to both feeding and social behavior; anorexia nervosa is a psychiatric illness defined by reduced food intake, weight loss, and problems in social perceptions. Oxytocin receptor single nucleotide polymorphisms rs2254298 or rs53576 and neural responses to social stimuli were evaluated in adult women with or recovered from anorexia nervosa using functional magnetic resonance imaging. Carriers of the A allele for OXTR rs2254298 (2 AA and 10 AG), showed significantly reduced activation of portions of the posterior cingulate cortex and medial prefrontal cortex for social stimuli, as well as greater negative connectivity between the posterior cingulate and the occipital lobe relative to the GG subjects for rs2254298. Differences in the other OXTR SNP, rs53576, did not result in detectable neural differences in either whole brain or region of interest analyses. Development of a mechanistic, biological model of how social behavior is impacted by mental illness requires linking genes to functional brain activations in disease. This pilot study suggests that in anorexia nervosa, differences related to OXTR SNP rs2254298 may alter neural responses to social stimuli and disrupt the engagement and disengagement of the default mode network.